FDTD Simulations of Sweat Ducts and Hair at 0.45 THz - Zoltan Vilagosh; Negin Foroughimehr; Alireza Lajevardipour; Andrew W. Wood (MDPI AG, 2023)
Advances in Terahertz frequency electromagnetic radiation (THz) production technologies have produced an increasing interest in exploring possible applications. New applications will inevitably lead to increased incidental interaction of humans with THz radiation. Given that the wavelength of THz radiation is in the same order of magnitude as the dimensions of skin structures such as hair and sweat ducts, the possibility of interaction among these structures is of interest. The interaction was studied utilizing Finite Difference Time Domain (FDTD) simulations using a far-field excitation of 0.45 THz. No antenna-like effects were detected. Regions of increased specific absorption rate (SAR) due to reactive near-field effects with both the hair and sweat ducts were found in the order of 0.01-0.05 mm and 0.001-0.002 mm, respectively. Simulations using unwound sweat ducts yielded the same penetration pattern as the helical structure, indicating that the helical structure has no impact on the propagation of THz radiation in skin.